2021
DOI: 10.2196/22802
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and User Feedback on a Gameful Breathing Training App: Within-Subject Experiment

Abstract: Background Slow-paced breathing training (6 breaths per minute [BPM]) improves physiological and psychological well-being by inducing relaxation characterized by increased heart rate variability (HRV). However, classic breathing training has a limited target group, and retention rates are very low. Although a gameful approach may help overcome these challenges, it is crucial to enable breathing training in a scalable context (eg, smartphone only) and ensure that they remain effective. However, desp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Furthermore, no significant differences were found regarding perceived effectiveness among the Breeze and Circle condition. Thus, the gameful visualization of Breeze had no impairing impact on the instrumental value of the breathing training, which is crucial as gamification should not reduce the instrumental value even if the experiential value increased [19,25]. These results are in line with our hypotheses and confirm results from previous work where the influences of gameful and nongameful breathing training on the physiological outcomes were investigated [27].…”
Section: Perceived Effectivenesssupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, no significant differences were found regarding perceived effectiveness among the Breeze and Circle condition. Thus, the gameful visualization of Breeze had no impairing impact on the instrumental value of the breathing training, which is crucial as gamification should not reduce the instrumental value even if the experiential value increased [19,25]. These results are in line with our hypotheses and confirm results from previous work where the influences of gameful and nongameful breathing training on the physiological outcomes were investigated [27].…”
Section: Perceived Effectivenesssupporting
confidence: 90%
“…The study compared Breeze (Error: Reference source not found), a gameful breathing training visualization, to a standard breathing training visualization, hereafter referred to as Circle (Error: Reference source not found). The standard breathing training visualization was adapted from previous studies, [15,19,27]. The videos that were used to instruct and guide the participants before and during breathing training can be found in Multimedia Appendences 1-4.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations